Mortality and causes of death after traumatic spinal cord injury in Estonia. (November 2013) - Sabre, Liis; Rekand, Tiina; Asser, Toomas; Kõrv, Janika
Abstract : Study design: Retrospective population-based study with mortality follow-up. Objective: To study mortality, causes and risk factors for death in Estonian patients with traumatic spinal cord injury (TSCI). Setting: All Estonian hospitals. Methods: Medical records of patients with TSCI from all regional, central, general, and rehabilitation hospitals in Estonia from 1997 to 2007, were retrospectively reviewed. Mortality status was ascertained as of 31 December 2011. Causes of death were collected from the Estonian Causes of Death Registry. Standardized mortality ratios (SMRs) were calculated for the entire sample and for causes of death. A Cox proportional hazards modeling was used to identify the risk indicators for death. Results: During the observation period (1997–2011) 162 patients of 595 died. Nearly half of the patients ( n  = 76) died during the first year after TSCI. The main causes of death were external causes (30%), cardiovascular disease (29%). and suicide (8%). The overall SMR was 2.81 (95% confidence interval 2.40–3.28) and SMR was higher for women than for men (3.80 vs. 2.70). Cause-specific SMRs were markedly elevated for sepsis and suicide. Mortality was significantly affected by the age at the time of injury, neurological level, and extent of the injury as well as the year of TSCI and complications. Conclusion: Life expectancy is significantly decreased in patients with TSCI in Estonia compared with the general population. Deaths during the first year after the injury have an important impact on statistics. Treatment of cardiovascular diseases, infections, and prevention of suicide are useful for reducing mortality in patients with TSCI.